The Effect of Contextual Factor on Learning Styles Preferences of English Majors in Lao Public Universities - Souksakhone Sengsouliya; Sithane Soukhavong; Say Phonekeo; Vanmany Vannasy; Vanthala Souvanxay; Chanmany Rattanavongsa (Journal of English Language Teaching and Linguistics, 2021)
This research is a quantitative correlational design, which investigates the English learning styles preferences of English major in Laotian public universities in Lao PDR and tests the effect of contextual factors on the participants’ learning styles preferences. The sample of this research involved 542 university-level students who major in English at a bachelor-degree program in four public universities in Lao PDR. The instrument of the study was Reid’s (1987) Perceptual Learning Style Preference Questionnaire (PLSPQ), which includes six different learning styles (Audio, Visual, Kinesthetic, Tactile, Individual, and Group learning styles). Participants were invited to rate their learning style preference towards the scale. The analysis was conducted based on Reid’s (1995) guide of categorizing preference levels, such as Major, Minor Learning Style Preference, and Negligible. The results indicated that the participants had three major preferences towards Kinesthetic learning (M=41.20), Audio learning (M=39.18), and Tactile learning styles (M=38.14), respectively. The study also found that there are significant differences in English learning styles preferences among students from different institutional contexts. Further research on testing the effect of contextual factors on learners’ learning choice is strongly recommended.